Preference for group work, winning orientation, and social loafing behavior in groups - Stark, Erik M.; Shaw, Jason D. (2007)
The authors developed a multilevel interactive model for predicting social loafing behavior in groups and tested this model in a study of 367 individuals working in 102 groups during a 4-month period. Study results revealed the importance of intergrating both person (preference for group work and winning orientation) and situation (task interdependence) factors in predicting social loafing. Preference for group work was consistently and negatively related to social loafing behavior (self-reported and peer rated), and this relationship was moderated by both winning orientation and task interdependence. As predicted, group members were more likely to self-report social loafing when their preference for group work and winning orientation were both low. Peer-rated social loafing was most likely when preference for group work, winning orientation, and task interdependence were all low, as predicted. Theoretical and practical implications of the results are addressed, and several directions for future research are outlined.
Downloaded from http://gom.sagepub.com/cgi/content/abstract/32/6/699.
Keywords: Social psychology; Individual competitiveness; Teams in the workplace; Attitude (Psychology).